Effectiveness and safety profile of fluticasone propionate 0.05% in paediatric dermatoses - Mohankar, Atul Dilip; Sinha, Mayank (International Journal of Research in Medical Sciences, 2024)
Background: Topical corticosteroids are effective in the treatment of paediatric dermatoses. However, concerns regarding possible side effects of topical steroids have limited the use of moderate-potency corticosteroids in children. Objective of this study was to evaluate the effectiveness and safety profile of fluticasone propionate 0.05% cream in paediatric dermatoses. Methods: A total 84 children between 6 months to 12 years of age with moderate to severe dermatoses (< or =30% body surface area) were treated with fluticasone propionate 0.05% cream twice daily for 4 to 6 weeks. Adverse effects of topical steroids were analyzed. Results: Out of total 84 patients, 46 (54.76%) patients completely cured at 4 weeks and 23 (27.38%) patients at 6 weeks, while remaining 11 (13.10%) patients showed moderate improvement, 4 were lost for follow up after 2 weeks. Only in 2 patients we observed hypopigmentatipon of skin, otherwise in all patients no significant side effect were seen. Conclusions: Fluticasone propionate 0.05% cream appears to be quite safe for the treatment of moderate to severe dermatoses for up to 4 to 6 weeks in children less than 12 years of age.